Perkembangan Bank Sentral : Status, Kedudukan, dan Tugas dari Bank Sentral - Rini Puji Astuti; Lisa Maretha Wulandari; Desi Duwi Safitri (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The role and function of Bank Indonesia as the central bank is crucial to revitalize the goal of maintaining and preserving the value of the rupiah, which is an important part of sustainable economic growth that will improve people's welfare. This goal is part of the economic recovery and reform policy that will help Indonesia get out of the middle economic crisis. The purpose of this study is to determine the development of the status, position, and duties of the central bank. This research uses the literature method. In 1968, Bank Indonesia's functions and responsibilities as the central bank began to diminish. In 1999, it was again responsible for safeguarding and maintaining the value of the rupiah. Its central bank work consists of three main pillars: setting and implementing monetary policy, maintaining a smooth payment system, and maintaining the stability of the national financial system. To improve people's quality of life, Bank Indonesia is also responsible for acting as a development agent.